The Effects Of Chemical Modification And Layering On Properties Of Woven And Nonwoven Kenaf Fiber Reinforced Epoxy Composites - Mohd Saad, Nurul 'Atiqah (2014)

(untitled)
The great potential of kenaf fiber combined with the new structure of woven and nonwoven fiber mat were reinforced in the epoxy resin by hand lay-up process. The design of stacking combination with different layering pattern of woven and nonwoven as a tri-layer composites was studied. Potensi tinggi gentian kenaf digabungkan dengan struktur baru tikar gentian anyaman dan bukan anyaman diperkuatkan dengan resin epoksi melalui proses ‘hand lay-up’. Reka bentuk kombinasi susunan dengan corak lapisan yang berbeza daripada anyaman dan bukan anyaman sebagai komposit tiga lapisan telah dikaji.